Implementasi Load Balance Menggunakan Metode Policy Based Route (PBR) Pada Politeknik Sawunggalih Aji Kutoarjo - Damar Eko Cahyono (Politeknik Sawunggalih Aji, 2022)
Load balance settings are very important if you have 2 or more ISPs for paths to the internet network. Load balance itself is useful for dividing the network load into several paths. Currently, Sawunggalih Aji Polytechnic uses an older version of the TP-Link Load Balance Router so it is less effective. This is what motivates the author to conduct research on the implementation of the load balance policy based route (PBR) method using a Mikrotik device. This study aims to increase the effectiveness of the load balance at the Sawunggalih Aji Polytechnic using routers of different brands. Research on load balance implementation uses at least 1 router and 2 ISPs. This research focuses on the application of the load balance concept using the policy based route method and testing it. The results of the load balance implementation using the policy based route method, namely the internet path traversed by the data packet according to the design that has been designed in the design chapter. These results are obtained from testing using the command prompt or the torch feature found on Mikrotik